PENGARUH BUDAYA ORGANISASI, TEAMWORK DAN WORK-LIFE BALANCE TERHADAP EMPLOYEE ENGAGEMENT DI PJK3 DAERAH ISTIMEWA YOGYAKARTA - Octa, Octavia Nurul Hidayah; Audita Nuvriasari (Jurnal Ilmu Manajemen (JIMMU), 2024)
This study aims to analyze the influence of organizational culture, teamwork, work-life balance on employee engagement at PJK3 in the Special Region of Yogyakarta. The research sampel was 46 respondents using the non probability sampling technique. Questionnaire instruments int the form of questionnaires were distributed through direct face-to-face with respondents. Data analysis tools using multiple linear regression. The results of the study prove that : (1) Organizational culture no significant effect on employee engagement in PJK3 Yogyakarta Special Region. (2) Teamwork has a positive and significant effect on employee engagement at PJK3 Yogyakarta Special Region. (3) Work-life balance has a positive and significant effect on employee engagement at PJK3 Yogyakarta Special Region